COMPARATIVE ANALYSIS OF SOLAR STREET LIGHTING SYSTEMS FOR SIX SELECTED LOCATIONS IN NIGERIA - DABAI K. A.; GARBA I.; ADAMU A. A.; JIMOH M. T. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
There is a desperate need for high-quality, affordable, and reliable lighting systems at sites where the electricity grid is either non-existent or unstable for applications such as security lighting. Many systems installed in Nigeria are failing due to poor design or wrong sizing of the components. This paper gives a detailed design and analysis of Stand-alone Solar Street Lighting Systems taking six selected locations in Nigeria as cases of the study for comparison. The variations of solar radiation and night lengths were considered. The monthly average solar radiation data were based on 22 years of monthly average insolation figures obtained from the National Aeronautics Space Administration (NASA). A single LED lamp rated 12V, 40W DC operating from dusk to dawn was used for the design. The results show that the length of nights varies seasonally with maximum values in December and minimum values in June for all the locations with places closest to the equator having the least variation. Components requirement indicates that a piece of 12V, 100Ah battery, and a piece of 12V, 20A charge controller will suffice for all the locations. The difference is based on solar array requirement in which the results show that 2 pieces of 120Wp solar panel connected in parallel will be adequate for PortHarcourt, and Benin-City; 2 pieces of 100Wp for Ibadan, and Makurdi; and 2 pieces of 80Wp for Kano and Maiduguri. The difference in the array requirement was based on the solar radiation available in the location, for those having higher radiation require less solar array and vice versa.